Association Between Leukocyte Telomere Length and the Risk of Incident Atrial Fibrillation: The Framingham Heart Study. Issue 11 (14th November 2017) - Staerk, Laila; Wang, Biqi; Lunetta, Kathryn L.; Helm, Robert H.; Ko, Darae; Sherer, Jason A.; Ellinor, Patrick T.; Lubitz, Steven A.; McManus, David D.; Vasan, Ramachandran S.; Benjamin, Emelia J.; Trinquart, Ludovic
Abstract : Background: Advancing age is a prominent risk factor for atrial fibrillation (AF). Shorter telomere length is a biomarker of biological aging, but the link between shorter telomere length and increased risk of AF remains unclear. We examined the association between shorter leukocyte telomere length (LTL) and incident AF. Methods and Results: We included AF‐free participants from the observational Framingham Heart Study Offspring cohort from 1995 to 1998, who had LTL measurements. We examined the association between baseline LTL and incident AF with multivariable Cox models adjusted for age, sex, current smoking, height, weight, systolic and diastolic blood pressure, use of antihypertensive medication, diabetes mellitus, history of myocardial infarction, and history of heart failure. The study sample comprised 1143 AF‐free participants (52.8% women), with mean age of 60±8 years. The mean LTL at baseline was 6.95±0.57 kb. During 15.1±4.2 years mean follow‐up, 184 participants (64 women) developed AF. Chronological age was associated with increased risk of AF (hazard ratio per 10‐year increase, 2.16; 95% confidence interval, 1.71–2.72). There was no significant association between LTL and incident AF (hazard ratio per 1 SD decrease LTL, 1.01; 95% confidence interval, 0.86–1.19). Our study was observational in nature; hence, we could not exclude residual confounding and we were unable to establish causal pathways. Conclusions: In our moderate‐sized community‐based cohort, we did not find evidence for a significant association between LTL and risk of incident AF.